Експресивне використання дефіса в художньому тексті (на матеріалі французької літератури ХХ століття) - Хайчевська, Тетяна Миколаївна; Khaichevska, Tetiana M. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У сучасному французькому писемному мовленні, зокрема у друкованих ЗМІ, інтернет-блогах, рекламі та художній літературі простежується тенденція до незвичного використання графічних засобів для опосередкованого впливу на сприйняття написаного читачем. У статті досліджено оригінальні випадки вживання дефіса, які показують його ефективність як інструмента передачі авторської експресії у художньому тексті, також зроблено спробу класифікувати та визначити найбільш поширені випадки експресивного використання дефіса. In contemporary French writing, mass media, world blogs, advertising and literature there is a tendency to the unusual applying of graphical means in order to have a knock-on effect on the acquisition of something written. This article deals with the investigation of the unusual hyphen use, that shows its effectiveness as a tool for the transfer of the author’s expression in fiction. The attempt to classify and identify the most common cases of the hyphen expressive use in the modern French written language was made. The results of the investigations showed that the hyphen’s expressive potential appears in the case of recording hyphenated letters or syllables of one word, for combining single words in compound words, phrases and sentences. Expressive use of the hyphen transmits various individual features of intonation and points out the rethinking of the text elements written with its help.
Expressive Use of Hyphen in a Fiction Text (on the Material of XX century French Literature)
Keywords: дефіс; hyphen; дефісація; hyphenation; графон; graphon